CAMPUHAN RIVER UBUD AS AN INSPIRATION FOR THE ARTISTS - I Wayan Karja (Proceeding Bali-Bhuwana Waskita: Global Art Creativity Conference, 2022)
The purpose of this research is to open awareness about the significant history of the Campuhan River in terms of aesthetic, the prosperity of the people's lives, both physically and spiritually. This qualitative research method took place in Campuhan Ubud, due to the limited sources of written data and art artifacts. Data collection was mostly done through direct interviews, books, and the internet. Furthermore, an analysis that focuses on the significance of the Campuhan River as an inspiration for the artists is carried out. Artists with high awareness capture the vibrations of natural energy by creating various styles of painting. Campuhan River has a certain vibration so that many artists are inspired to create paintings in various styles such as the Pita Maha style, Young Artist, impressionism, and expressionism. The implications of the Campuhan River civilization as inspiration are an asset for the surrounding area.